Perceptions towards private tuition across races in Singapore. - Ng, Suet Hui. (2008)
The research was undertaken to find out the different perceptions towards private tuition in Singapore. The results were used to suggest to tuition agencies and centres how they can customise their marketing srategies to the different races in Singapore.